Routine growth monitoring processes in nutrition programs in India have multiple falter points with implications for quality of care - Bajaj, Sumati; Avula, Rasmi; Pant, Anjali; Nguyen, Phuong Hong; Ruel, Marie T.; Menon, Purnima (American Society for Nutrition, 2020)
Growth monitoring (GM) and promotion is a routine part of primary healthcare for children in >80% of countries. In India, 57.5 million children are measured every month by frontline workers to assess their growth and to trigger preventive or curative services. Standard guidance for anthropometry suggests that quality can be compromised by the choice of measurement equipment, placement of equipment, and positioning of children during measurement. Little is known about the quality of measurement processes during GM. We compared child height and weight measurement processes with standards for anthropometry to assess GM quality.